Exploring the astrophysical conditions for the creation of the first r-process peak, and the impact of nuclear physics uncertainties - Nikas, Stylianos; Martínez-Pinedo, G.; Wu, M. R.; Sieverding, A.; Reiter, M. P. (HNPS Advances in Nuclear Physics, 2020)
We present a study of nucleosynthesis for conditions of high Ye outflows from Neutron Star Mergers (NSMs). We investigate the effect of new beta-decay rates measurements and uncertainties in nuclear masses of the newly measured 84,85 Ga to the r-process nucleosynthesis calculations. The impact of these quantities to the production of the elements of the r-process abundance pattern for A < 100 is quantified and presented.